Pure Butane as refrigerant in domestic refrigerator freezer - Sattar, M.A.; Saidur, Rahman; Masjuki, Haji Hassan (Greater Mekong Subregion Academic And Research Network, 2007)
This paper presents an experimental investigation on the performance of a domestic refrigerator using pure butane as a refrigerant. A domestic refrigerator designed to work with R-134a as refrigerant was used as test unit to assess the possibility of pure butane as refrigerant. The experiments are conducted with the refrigerants under the same no load condition at a surrounding temperature of 25°C and 28°C. The refrigeration capacity, the compressor power, the coefficient of performance (COP), condenser duty and heat rejection ratio were investigated. The performance parameter and power consumption of the refrigerator when R-134a was used as refrigerant is considered as baseline. The performance of pure butane is compared with the performance of R-134a. The compressor consumes 2.08kWh/day and 2.25kWh/day when R-134a is used refrigerant but when butane is used it consumes 2.197kWh/day and 2.199kWh/day at 25°C and 28°C ambient temperature respectively. The result shows a better performance of butane than R-134a. The results support the possibility of using butane as an alternative to R-134a in domestic refrigerators, without any modification of the domestic refrigerator.